As práticas comunicacionais do pós-venda: o SAC na era das redes sociais on-line - LAHOZ, DEISE BALEK (2016)
Study on the communication practices of post-sales area in social networks on-line, regarding the service of companies and channels available for interaction to the consumers. Among the steps, there was an analysis of consumer habits to conduct searches on social networks on-line; in order to draw the attention of companies on after-sales problems in these channels (complaints, technical questions, suggestions, etc.). The main objective was to develop chronologically and structured communication practices in after-sales through various channels of SAC; recovering the evolutionary phases of the SAC, consumer protection law, since the analog era (without internet access and spontaneous), until the arrival of social networking online. For this study were performed: bibliographic, exploratory and documental survey on the area of after-sales, relationship marketing and research results on the habits of consumers connected to the Internet; presentation of cases that exemplify the communication market practices; interview applied with eight market experts; and electronic form applied with managers of call centers. With all of these analyzes, it was possible to draw a diagnosis of the current situation of the customer service area of the selected companies in the online social networks, in addition to significantly reinforce the idea of consumer content producer (prosumer) and the change in the flow communicational consumer versus business.